From strategy to action: a qualitative study on salient factors influencing knowledge transfer in project-based experiential learning in healthcare organisations in Kenya. Issue 9 (30th September 2019) - Chelagat, Tecla; Onyango, Joseph; Kokwaro, Gilbert; Rice, Jim
Abstract : Objectives: Knowledge transfer is recognised as a key determinant of organisational competitiveness. Existing literature on the transfer of knowledge and skills imply diminutive return on investment in training and development due to the low application of learnt knowledge. Following devolution of health services provision to new counties in Kenya in 2013, Strathmore Business School designed an experiential facility improvement project-based leadership training programme for healthcare managers in the new counties. Selected healthcare management teams participated in the leadership training to improve health systems performance in the devolved counties in Kenya. Despite similar training, the projects implementation contexts were different, leading to different implementation completion rates. The aim of this study was to investigate the reasons for this disparity and then recommend solutions. Design: A qualitative study using semi-structured interviews. A thematic framework approach was used in data analysis. Setting and participants: Thirty-nine projects teams constituting; 33 successful and 6 unsuccessful project teams, were purposively selected based on their project implementation success rates at the end of the leadership training. The managers had undertaken a team-based institutional improvement project. The prioritised projects were housed within; 23 public, 10 faith-based and 6 private health facilities in 19 counties in Kenya. Results: Our findings indicate projects completion rates were influenced by (training design, work environment climate, trainee characteristics, team-based coaching and leveraging on occurring opportunities). Transfer barriers were (inadequate management support, inadequate team and staff support, high staff turnover, misalignment of board's verses manager's priorities, missing technical expertise, endemic strikes, negative politics and poor communication). Recommendations were (need-driven curriculum, effective allocation and efficient utilisation of resources, proper prioritisation, effective communication, longitudinal coaching and work-teams recruitment). Conclusion: The findings reveal that unless training interventions are informed by a need-driven curriculum customised to real-world work teams, the potential knowledge and skill transfer can be thwarted.